AKT/mTOR as Novel Targets of Polyphenol Piceatannol Possibly Contributing to Inhibition of Proliferation of Cultured Prostate Cancer Cells. (3rd April 2012) - Hsieh, Tze-Chen; Lin, Chia-Yi; Lin, Hung-Yun; Wu, Joseph M.
Abstract : The polyphenol piceatannol has shown inhibition against tyrosine and serine/threonine kinases. Whether piceatannol also exerts activity on the mammalian target of rapamycin (mTOR), a kinase involved in growth control of eukaryotic cells, is not known. In this study, we tested the effects of piceatannol on proliferation of androgen-dependent (AD) LNCaP and androgen-independent (AI) DU145 and PC-3 prostate cancer (CaP) cells. Suppression of AD and AI CaP cell growth by piceatannol was accompanied by cell cycle blockade in G1 /S and S phases for LNCaP and PC-3 and induction of apoptosis in DU145 cells. Induction of apoptosis by piceatannol in DU145 cells was evident by reduced expression of poly(ADP-ribose) polymerase (PARP), cleavage of caspase 3 and apoptosis inducing factor AIF, and an increase in cytochrome c. The apoptotic changes occurred in concordance with DNA damage, supported by increased phosphorylated histone H2AX. Immunoblot analyses showed that exposure of different-stage CaP cells to piceatannol also resulted in cell-type-specific downregulation of mTOR and its upstream and downstream effector proteins, AKT and eIF-4E-BP1. We propose that the observed AKT and mTOR changes are new targets of piceatannol possibly contributing to its inhibitory activities on proliferation of CaP cells.